Revestimentos comestíveis com óleos essenciais na preservação da qualidade pós-colheita de morangos: uma revisão - Calisto, Ítalo Henrique (Universidade Federal de São Carlos, 2021)
Strawberry is a non-climacteric fruit characterized by its unique flavor, being highly desirable and being a relevant source of bioactive compounds due to the high levels of vitamin C, vitamin E and phenolic compounds, as well as anthocyanins, pigments that give the strawberry its red color and are related to health benefits. The application of edible coatings on the surface of the food is a treatment that allows to increase the shelf life of the food with little effect on its original characteristics. These coatings may contain active ingredients in their composition, such as essential oils that can confer antimicrobial properties to these materials. This study aimed to review the state of the art on the application of edible coatings associated with essential oils in the preservation of postharvest quality of strawberries. The results showed that the application of edible coatings with essential oils can improve the quality parameters of strawberries during storage and control the development of post-harvest diseases. In this way, the application of these materials can be a promising alternative to replace synthetic chemical fungicides for disease control and prolonging the shelf life of strawberries.
Edible coatings with essential oils in the preservation of postharvest quality of strawberries: a review
Keywords: Morango; Revestimento comestível; Óleos essenciais; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS